Generalised pruritus as a presentation of Grave’s disease - Tan CE; Loh KY (Malaysian Family Physician, 2013)
Pruritus is a lesser known symptom of hyperthyroidism, particularly in autoimmune thyroid disorders. This is a case report of a 27-year-old woman who presented with generalised pruritus at a primary care clinic. Incidental findings of tachycardia and a goiter led to the investigations of her thyroid status. The thyroid function test revealed elevated serum free T4 and suppressed thyroid stimulating hormone levels. The anti-thyroid antibodies were positive. She was diagnosed with Graves’ disease and treated with carbimazole until her symptoms subsided. Graves’ disease should be considered as an underlying cause for patients presenting with pruritus. A thorough history and complete physical examination are crucial in making an accurate diagnosis. Underlying causes must be determined before treating the symptoms.